212‐Gbit/s 2:1 multiplexing selector realised in InP DHBT. Issue 5 (1st March 2019) - Konczykowska, A.; Jorge, F.; Riet, M.; Nodjiadjim, V.; Duval, B.; Mardoyan, H.; Estaran, J.M.; Adamiecki, A.; Raybon, G.; Dupuy, J.‐Y.
Abstract : In this Letter, the authors report on the design, optimisation and electrical measurements of a new fully integrated multiplexing selector fabricated in 0.7‐µm indium phosphide (InP) double‐heterojunction bipolar transistor technology. All parts of the circuit were optimised to obtain 200‐Gbit/s class of operation. They present electrical performances at 140 and to a record speed of 212 Gbit/s, highlighting their respective measurement challenges. The power consumption of the circuit is 0.5 and 0.8 W for a differential output amplitude of 240 and 730 mV, respectively. This selector has been successfully used as modulator driver in optical transmission experiments up to 204 Gbit/s.